Duplex ultrasonography for the detection of vertebral artery stenosis: A comparison with CT angiography. Issue 8 (29th June 2017) - Rozeman, Anouk D.; Hund, Hajo; Westein, Michel; Wermer, Marieke J. H.; Lycklama à Nijeholt, Geert J.; Boiten, Jelis; Schimsheimer, Robert‐Jan; Algra, Ale
Abstract: Objectives: Vertebrobasilar stenosis is frequent in patients with posterior circulation stroke and it increases risk of recurrence. We investigated feasibility of duplex ultrasonography (DUS) for screening for extracranial vertebral artery stenosis and compared it with CT angiography (CTA). Materials and Methods: We gathered data on 337 consecutive patients who had DUS because of posterior circulation stroke or TIA. Matching CTA studies were retrieved and used as reference. Stenosis on CTA was considered "significant" if >50%, at DUS if Peak Systolic Velocity (PSV) > 140 cm/s for the V1 segment and PSV > 125 cm/s for the V2 segment. We determined the area under the ROC curve (AUROC). In addition, we calculated which PSV cut‐off value resulted in highest sensitivity with acceptable specificity. Results: DUS was able to make an adequate measurement in 378 of 674 V1 segments and 673 of 674 V2 segments. DUS detected a significant stenosis in 52 of 378 V1 segments; 12 were confirmed by CTA (AUROC 0.73, 95% Confidence Interval 0.63–0.83). The optimal DUS PSV cut‐off value for this segment was 90 cm/s. For the V2 segment there were too few stenoses to allow reliable assessment of diagnostic characteristics of DUS. Conclusions: Although DUS has a fair AUROC for detecting significant stenosis, adequate assessment of the V1 segment is often not possible due to anatomic difficulties. Assessment of the V2 segment is feasible but yielded few stenoses. Hence, we consider usefulness of DUS for screening of extracranial vertebral artery stenosis limited. Abstract : Although duplex ultrasonography is fairly capable of detecting significant extracranial vertebral artery stenosis, adequate assessment of the V1 segment is often not possible due to anatomic difficulties. Assessment of the V2 segment is feasible but yielded few stenoses. Hence, we consider usefulness of DUS for screening of extracranial vertebral artery stenosis limited.